Serum IgG subclass levels and risk of exacerbations and hospitalizations in patients with COPD - Leitao Filho, Fernando S; Ra, Seung W; Mattman, Andre; Schellenberg, Robert S; Criner, Gerard J; Woodruff, Prescott G; Lazarus, Stephen C; Albert, Richard; Connett, John E; Han, Meilan K; Martinez, Fernando J; Leung, Janice M; et al. (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background The literature is scarce regarding the prevalence and clinical impact of IgG subclass deficiency in COPD. We investigated the prevalence of IgG subclass deficiencies and their association with exacerbations and hospitalizations using subjects from two COPD cohorts. Methods We measured IgG subclass levels using immunonephelometry in serum samples from participants enrolled in two previous COPD trials: Macrolide Azithromycin for Prevention of Exacerbations of COPD (MACRO; n = 976) and Simvastatin for the Prevention of Exacerbations in Moderate-to-Severe COPD (STATCOPE; n = 653). All samples were collected from clinically stable participants upon entry into both studies. IgG subclass deficiency was diagnosed when IgG subclass levels were below their respective lower limit of normal: IgG1 < 2.8 g/L; IgG2 < 1.15 g/L; IgG3 < 0.24 g/L; and IgG4 < 0.052 g/L. To investigate the impact of IgG subclass levels on time to first exacerbation or hospitalization, we log-transformed IgG levels and performed Cox regression models, with adjustments for confounders. Results One or more IgG subclass deficiencies were found in 173 (17.7%) and 133 (20.4%) participants in MACRO and STATCOPE, respectively. Lower IgG1 or IgG2 levels resulted in increased risk of exacerbations with adjusted hazard ratios (HR) of 1.30 (95% CI, 1.10–1.54, p < 0.01) and 1.19 (95% CI, 1.05–1.35, p < 0.01), respectively in the MACRO study, with STATCOPE yielding similar results. Reduced IgG1 or IgG2 levels were also associated with increased risk of hospitalizations: the adjusted HR for IgG1 and IgG2 was 1.52 (95% CI: 1.15–2.02, p < 0.01) and 1.33 (95% CI, 1.08–1.64, p < 0.01), respectively for the MACRO study; in STATCOPE, only IgG2 was an independent predictor of hospitalization. In our multivariate Cox models, IgG3 and IgG4 levels did not result in significant associations for both outcomes in either MACRO or STATCOPE cohorts. Conclusions Approximately 1 in 5 COPD patients had one or more IgG subclass deficiencies. Reduced IgG subclass levels were independent risk factors for both COPD exacerbations (IgG1 and IgG2) and hospitalizations (IgG2) in two COPD cohorts. Trial registration This study used serum samples from participants of the MACRO ( NCT00325897 ) and STATCOPE ( NCT01061671 ) trials.